STUDI SEMIEMPIRIS STRUKTUR MOLEKUL DAN BAND GAP MONOMER DAN DIMER 1,3,4 TIADIAZOL DAN DERIVATNYA - Emdeniz - (Universitas Andalas, 2010)
In order to know the possibility of compounds and their derivative for semiconductor material, moleculer structure and band gap (Eg) of these compounds need to be studied. This work included 1,3,4 tiadiazole and 1,3,4 tiadiazole derivative with –C≡N and –C≡CH substituents. Each compounds was optimized by Calzaferri methods. The calculation results show that monomers and dimers 1,3,4 tiadiazole and thair derivative have Eg in the range of 2.89760 eV to 4.35801 eV. These compounds has potential for basis of material organic semiconductor. Keywords: Semiconductor, Band gap, Tiadiazole.